Utilization of auto-flocculate of microalgae Scededesmus sp. for harvesting of freshwater microalgae Chlorella sp. biomass - Nurfarahana Mohd Nasir (2021)
Currently, Microalgae has contributed to the sustainable development of industries includes biofuel industry, the pharmaceutical industry, wastewater treatment industry and others. With increasing knowledge regarding a variety of microalgae uses results in high interest among people in the world to harvest microalgae. Harvesting of commercial microalgae is normally done by centrifugation, gravity filtration, ultrafiltration and other methods which require high costs. Therefore, the harvesting of Chlorella sp by bioflocculation method which involves autoflocculating microalgae, Scenedemus sp with lower cost was introduced. The removal efficiency >80 % and biomass recovery >75% were achieved for coagulation-flocculation of Scenedesmus sp to harvest Chlorella sp. Results of this study showed that the utilization of auto-flocculate microalgae in microalgae biomass harvesting could abridge downstream processing, redeemable resources and would reduce the production cost for future microalgae-based.